Achilles tendon dimensions, ankle stiffness and footfall patterns in recreational runners - Skypala, Jiri; Monte, Andrea; Hamill, Joseph; Plesek, Jan; Jandacka, Daniel (Journal of sports sciences, 2023)
The main purpose of this study was to investigate the relationship among Achilles tendon (AT) dimensions, ankle joint stiffness, and footfall patterns in recreational rearfoot and non-rearfoot runners. Based on the foot strike index, a total of 107 runners were divided into rearfoot (47 females/40 males) and non-rearfoot runners (14 females/6 males). All participants had theirs AT dimensions (AT length, AT thickness, and AT moment arm) measured using a combination of ultrasound and motion capture systems. In addition, all performed running trials measured at self-selected speed in laboratory-neutral shoes. A partial correlation coefficient was used for correlations between the selected variables. The results revealed a significant relationship between ankle joint stiffness and level of footfall pattern in rearfoot (r = 0.232, p = 0.032) and non-rearfoot runners (r = -0.811, p < 0.001). The results also suggest a relationship between AT thickness and foot strike index (r = -0.486) in non-rearfoot runners. Runners whose footfall pattern is closer to the heel have greater ankle joint stiffness. Non-rearfoot runners whose footfall pattern is closer to the toe have a thinner AT. Non-rearfoot runners with thicker AT had greater ankle joint stiffness.
Keywords: biomechanika; dolní končetina; Humans; lidé; kotník; non-rearfoot runners; rearfoot runners; Running; Female; Male; Achilles Tendon; Achilles tendon moment arm; Ankle; noha (od hlezna dolů); mužské pohlaví; Foot; Achilles tendon length; ženské pohlaví; Achillova šlacha; Biomechanical Phenomena; Lower Extremity; Achilles tendon thickness